Promising Therapeutic Candidate for Myocardial Ischemia/Reperfusion Injury: What Are the Possible Mechanisms and Roles of Phytochemicals? - Chen, Cong; Yu, Lin-Tong; Cheng, Bai-Ru; Xu, Jiang-Lin; Cai, Yun; Jin, Jia-Lin; Feng, Ru-Li; Xie, Long; Qu, Xin-Yan; Li, Dong; Liu, Jing; Li, Yan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Percutaneous coronary intervention (PCI) is one of the most effective reperfusion strategies for acute myocardial infarction (AMI) despite myocardial ischemia/reperfusion (I/R) injury, causing one of the causes of most cardiomyocyte injuries and deaths. The pathological processes of myocardial I/R injury include apoptosis, autophagy, and irreversible cell death caused by calcium overload, oxidative stress, and inflammation. Eventually, myocardial I/R injury causes a spike of further cardiomyocyte injury that contributes to final infarct size (IS) and bound with hospitalization of heart failure as well as all-cause mortality within the following 12 months. Therefore, the addition of adjuvant intervention to improve myocardial salvage and cardiac function calls for further investigation. Phytochemicals are non-nutritive bioactive secondary compounds abundantly found in Chinese herbal medicine. Great effort has been put into phytochemicals because they are often in line with the expectations to improve myocardial I/R injury without compromising the clinical efficacy or to even produce synergy. We summarized the previous efforts, briefly outlined the mechanism of myocardial I/R injury, and focused on exploring the cardioprotective effects and potential mechanisms of all phytochemical types that have been investigated under myocardial I/R injury. Phytochemicals deserve to be utilized as promising therapeutic candidates for further development and research on combating myocardial I/R injury. Nevertheless, more studies are needed to provide a better understanding of the mechanism of myocardial I/R injury treatment using phytochemicals and possible side effects associated with this approach.